Ebbaibbo: Emmboosi ya nasaae - Bible Society of Uganda (Kampala The Bible Society of Uganda, 2019)
Approval for Printing the Samia-Lugwe and oluheehe Bible was granted by Most Rev.Dr. Emmanuel obbo, A.J. ArchBishop of Tororo.
The Bible in Lusamia, An interconfessional Translation published as Ebbaibbo ; Emboosi ya Nasaae Ebitabo Bilaangwa Deuterokanoniko.
Keywords: Bible- Lusamia; Scripture--Samia-Lugwe--Uganda